215 Treatment outcomes of early carcinoma cervix before and after subspecialisation. (18th September 2019) - Thomas, V; Thomas, D; Sebastian, A; Thomas, A; Chandy, R; Peedicayil, A; Samuel, TR; Kumar, RM
Abstract : Objectives: This study aims to compare the treatment outcomes in carcinoma cervix before and after gynecologic oncology subspecialisation in a tertiary care hospital, in India. Methods: A retrospective cohort study comparing women with operable cervical cancer who underwent radical hysterectomy before and after gynaecologic oncology subspecialization. Electronic medical records of women operated for early carcinoma cervix between 2001- 2010 (59) and 2011- 2015 (74) were reviewed and compared for outcomes. Results: Seventy four patients were operated over 5 years after subspecialisation as against 59 over 10 years, with similar clinical characteristics (table 1 ) but with significant usage of three dimensional imaging (66% versus 38%). After surgical-pathological examination, both cohorts were comparable with regard to mean tumour size, lymph nodes retrieved, lymph nodal, parametrial, vaginal margin and lymphovascular space involvement, and deep stromal invasion (table 2 ). However, lymphovascular space involvement was not reported in 66% (39/59) in the 2001–2010 cohort. After subspecialisation, the rate of intraoperative (3% versus 14%, p=0.018) and postoperative complications (15% versus 46%, p=0.0004) were lower. Adjuvant radiation was used more after subspecialisation (50% versus 24%, p= 0.00). Concurrent chemoradiation was not used in the 2001–2010 group. The follow up rates were similar in both groups with comparable 3-year recurrence-free survival and overall survival rates (table 3 ). Conclusions: Gynaecological oncologic subspecialisation decreased intraoperative and postoperative complications and improved pathological reporting with appropriate tailoring of adjuvant therapy. However, increased rates of adjuvant treatment did not translate into better survival.